Gender Differences in Reaction to Psychological Pressure: Evidence from Tennis Players - Maria De Paola; Vincenzo Scoppa (Institute for the Study of Labor (IZA), 2015)
Using data on about 35,000 professional tennis matches, we test whether men and women react differently to psychological pressure arising from the outcomes of sequential stages in a competition. We show that, with respect to males, females losing the first set are much more likely to play poorly the second set, choking under the pressure of falling behind and receiving negative feedback. The gender differential is stronger in high stakes matches. On the other hand, when players are tied in the third set we do not find any gender difference in players' reactions: this suggests that females do not tend to choke if they do not lag behind. These results are robust controlling for measures of abilities and fitness of players, such as players' rankings, players' ex-ante winning probability, players' rest, players' and tournaments' fixed effects.
Keywords: J16; D03; L83; 330; gender differences; psychological pressure; choking under pressure; feedback; tennis